PERFORMANCE OF BUMDES MANAGERS IN UTILIZING DIGITAL TECHNOLOGY: A QUALITATIVE STUDY OF BUMDES GLOBAL BINTANG TIMUR, TEFA'O VILLAGE - Desman Gea; Meiman Hidayat Waruwu; Fatolosa Hulu; Yamolala Zega (LPPM YPITI, 2026)
Improving the performance of Village-Owned Enterprise (BUMDes) managers is a crucial foundation for realizing independent and competitive villages amidst the increasingly rapid flow of global digitalization. BUMDes managers are expected to possess more than just technical skills in managing business units. However, reality shows that BUMDes managers still face challenges in managerial aspects and digital literacy, which impact low productivity. This study uses a qualitative approach with descriptive methods. The purpose of this study is to analyze the performance of Bumdes Global Bintang Timur managers in utilizing digital technology. The qualitative approach was chosen because it can provide an in-depth understanding of the phenomena occurring in the field, particularly related to how digital technology is utilized by these Bumdes managers. Interviews with BUMDes Global Bintang Timur managers revealed that the use of technology in business management is still limited and tends to be manual. The process of recording and reporting finances is still carried out conventionally using notebooks and simple spreadsheets such as Excel. Although familiar with several digital applications, managers have not actively integrated technology into all BUMDes operational processes. The performance of BUMDes Global Bintang Timur managers in utilizing digital technology is still suboptimal. The main obstacles include low digital literacy, minimal training, the absence of digital SOPs, and limited infrastructure. A strategy is needed to increase human resource capacity, technical assistance, and utilize technology to support the efficiency and transparency of BUMDes management.